PENENTUAN KONTRAK OPSI TIPE EROPA MENGGUNAKAN MODEL SIMULASI VARIANCE GAMMA (VG) - PITRAYANI, NI KADEK LANI; DHARMAWAN, KOMANG; WIDANA, I NYOMAN (E-Jurnal Matematika; Vol 12 No 3 (2023), 2023)
Options are used as a hedge against stock price uncertainty brought on by unstable stock prices fluctuation. The price of an option contract can be determined using a variety of approaches, one of which is the Variance Gamma. The purpose of this study is to compare the Black Scholes method with the Variance Gamma simulation model to determine the European call option contract price. The first thing that needs to be done is to figure out the moment variance gamma method. These parameters were used as initial values to get an idea of what the parameters that will be used in the simulation will be like. The European call option contract's price is calculated using the simulation results, which are then compared to the Variance Gamma simulation model and the Black Scholes model for the European call option contract. This study shows that the European call option contract's price, which was calculated using the Variance Gamma simulation, is less expensive than the Black Scholes contract's price.